2019
DOI: 10.1111/crj.13006
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum levels of systemic inflammatory markers are linked to greater inspiratory muscle dysfunction in COPD

Abstract: Background Chronic obstructive pulmonary disease (COPD) is associated with an inflammatory response that becomes more pronounced in acute exacerbations. Considerable attention has recently focused on the value of several inflammatory mediators in predicting worsening of COPD‐related symptoms. Whereas respiratory muscle dysfunction is also widely present in this population, little is known about how systemic inflammation relates to inspiratory muscle dysfunction in COPD. Methods Fifty‐three males with mild‐to‐v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies, we found that the elevated levels of Cys C were significantly correlated with disease status and lung function. Hu et al [24] found that the elevated Cys C levels was an important and independent risk factor of increased mortality in a hospital setting during COPD exacerbation, Formiga et al [51] indicated that inspiratory muscle function was reduced with greater degrees of inflammation in COPD as expressed higher levels of Cys C. Combining with the results of previous studies and this meta-analysis, we thought that the elevated levels of serum Cys C might indicate the exacerbation and progression of COPD.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with previous studies, we found that the elevated levels of Cys C were significantly correlated with disease status and lung function. Hu et al [24] found that the elevated Cys C levels was an important and independent risk factor of increased mortality in a hospital setting during COPD exacerbation, Formiga et al [51] indicated that inspiratory muscle function was reduced with greater degrees of inflammation in COPD as expressed higher levels of Cys C. Combining with the results of previous studies and this meta-analysis, we thought that the elevated levels of serum Cys C might indicate the exacerbation and progression of COPD.…”
Section: Discussionsupporting
confidence: 60%
“…14 Other studies showed increased circulating SAA concentration in COPD and other pulmonary diseases such as idiopathic pulmonary fibrosis (IPF). [22][23][24] Formiga et al reported that inspiratory muscle performance was considerably lower in COPD patients with greater SAA concentration. 23 In addition, SAA was greater in patients with IPF than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Formiga et al reported that inspiratory muscle performance was considerably lower in COPD patients with greater SAA concentration. 23 In addition, SAA was greater in patients with IPF than in healthy controls. 22 Furthermore, serum levels of SAA and CRP together with other inflammatory markers (eg, IL-6, IL-8, TNF-a, IP-10) were significantly greater in COPD patients experiencing an exacerbation than during remission and in healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that SAA is dramatically increased during acute phase of a COPD exacerbation, and that SAA is a sensitive biomarker for exacerbation severity in COPD patients 14 . Other studies showed increased circulating SAA concentration in COPD and other pulmonary diseases such as idiopathic pulmonary brosis (IPF) [22][23][24] . Formiga et al reported that inspiratory muscle performance was considerably lower in COPD patients with greater SAA concentration 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed increased circulating SAA concentration in COPD and other pulmonary diseases such as idiopathic pulmonary brosis (IPF) [22][23][24] . Formiga et al reported that inspiratory muscle performance was considerably lower in COPD patients with greater SAA concentration 23 . In addition, SAA was greater in patients with IPF than in healthy controls 22 .…”
Section: Discussionmentioning
confidence: 99%